Gender inequality in the labor market in South Korea - А. Sabitkyzy (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2023)
This article explores the issue of gender inequality in the labor market in South Korea. Using a mixed-methods approach, the study provides a comprehensive understanding of the nature and extent of gender disparities in employment and career advancement. The research findings highlight that women in South Korea face a range of challenges in the labor market, including underrepresentation in high-skilled, high-paying jobs, limited access to training and development opportunities, and gender-based discrimination. The study also identifies key factors contributing to gender disparities, such as gender stereotypes and biases in the workplace. The article suggests policy interventions that promote gender diversity and inclusion in the workplace, provide women with access to training and development opportunities, and implement family-friendly workplace policies. The study's findings have important implications for policymakers, employers, and civil society organizations working to promote gender equality and women's empowerment in South Korea. Overall, the article underscores the need for sustained efforts to address gender inequality in the labor market, and the critical role of policy interventions in promoting gender diversity and inclusion in the workplace to achieve gender equality and promote social progress.